2018
DOI: 10.1002/chem.201802343
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Effect of Different Metal Centers in Metal–Organic Frameworks and Their Adsorption of Aromatic Molecules using Experimental and Simulation Studies

Abstract: In this study, the adsorption behavior of different metal centers in analogous M-1,4-NDC frameworks (1,4-NDC=1,4-naphthalenedicarboxylate) towards guest molecules through simulation studies and experimental studies is reported. Simulation studies showed that the adsorption behavior of analogous M-1,4-NDC is affected by the atomic radius of the metal center, which was found to be in agreement with the experimental studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The study highlighted the complexity in achieving adequate predictions for the microextraction performance, with successful results mainly linked to the pore environment, pore size, and pore aperture widths of the MOF, together with a clear influence of the metal nature. The nature of the metal of the MOF and its influence in extraction studies have also been quite recently pointed out by Lirio et al [ 14 ], with high importance given to the radius of the metal.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The study highlighted the complexity in achieving adequate predictions for the microextraction performance, with successful results mainly linked to the pore environment, pore size, and pore aperture widths of the MOF, together with a clear influence of the metal nature. The nature of the metal of the MOF and its influence in extraction studies have also been quite recently pointed out by Lirio et al [ 14 ], with high importance given to the radius of the metal.…”
Section: Introductionmentioning
confidence: 93%
“…UiO-66 has shown promising adsorption capacities for organic contaminants such as organic dyes [ 12 ] and for inorganic pollutants such as heavy metals [ 13 ]. However, the adsorption behavior of emerging pollutants, such as pharmaceutical and personal care products on UiO-66 has been scarcely studied [ 14 ], and to the best of our knowledge, there are not studies dealing with functionalized UiO-66 materials in microextraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies using MOFs in D-µSPE have pointed out the complexity of the systems, indicating the pore environment, pore size, and pore aperture widths of the MOF as the most influential factors, together with a clear influence of the metal nature (particularly the presence of unsaturated metal sites) [11]. Lirio et al also pointed out the influence of the metal, particularly the radius of the metal [13]. Taima-Mancera et al showed the positive effects of incorporating polar functionalities in the organic ligand of the MOFs used in D-µSPE when intending to extract polar analytes of a small size [12], with this idea having been further expanded by Boontongto et al to other application studies for polar analytes [14].…”
Section: Introductionmentioning
confidence: 99%